Estimating of Maximum Groundwater Level to Trigger Landslide in Batu Hijau Open Pit Mine, West Nusa Tenggara, Indonesia - Amirul Aiman Abd Karim; Wahyu Wilopo; I Gde Budi Indrawan; Yan Adriansyah (Geological Engineering Department Universitas Gadjah Mada, 2021)
The safety of the employees is essential in the mining activity area. Thus, the sloping wall of the pit needs to evaluate from time to time to avoid any loss due to landslide. One of the essential parameters to lead to slope failure is groundwater. Therefore, this paper highlights the limitations of the groundwater for the existing slope mine by analyzing it for several groundwater levels until it reached a safety factor below 1.2. The analysis was done using a finite element method for slope stability and finite element analysis for groundwater seepage for groundwater modeling. The results show that the safety factor of the slope showing a linearly decreasing trend and safety factor reached below 1.2 when 70 m increment in groundwater level from the original groundwater level model.